Analisis Desain Pekerjaan Masinis dalam Transformasi Digital pada PT Kereta Api Indonesia (Persero) - Hilma Harmen; Mishul Jayana; Nazwa Shafina; Kholillah Azahra Barus; Ria Novita (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2026)
Digital transformation has become a key strategy in enhancing efficiency, safety, and service quality in the public transportation sector, including PT Kereta Api Indonesia (Persero). This study analyzes the implementation of job analysis and design in supporting digital transformation, particularly in the position of train operators, which has undergone significant changes due to the implementation of automated systems such as Communication Based Train Control (CBTC), Automatic Train Protection (ATP), and Automatic Train Operation (ATO). The results show a shift in the role of train operators from direct controllers to system supervisors, with competencies focusing on digital literacy, risk analysis, and technology-based decision-making. This change also impacts work patterns, where train operators now focus more on system monitoring and troubleshooting rather than manually controlling the trains. This transformation encourages a more adaptive, integrative, and safety-oriented job design while creating new roles in technology and data management. The success of digital transformation depends not only on the application of cutting-edge technology but also on job designs that are responsive to operational changes and evolving human resource needs. The synergy between technological innovation and effective job design is key to creating a safer, more efficient, and sustainable transportation system in the future